Neurolinguistic programming (NLP): its overview and review in the lenses of philosophy and pedagogy / Anis Shaari and Aswati Hamzah - Shaari, Anis; Hamzah, Aswati (Universiti Teknologi MARA, 2016)
Standing for Neurolinguistic Programming, the acronym ‘NLP’ has become an emergent approach to communication and personal development which has gained worldwide interest. Containing a set of strategies that is highly claimed to be effective in enhancing oneself personally, NLP has also become progressively more recognisable in the education sector. Nevertheless, NLP is still considered to be virtually absent from the academic realm, particularly in relation with learning and pedagogy. This silence suggests a dire need to expand academic practices studying and discussing NLP. Hence, this paper depicts the current state of knowledge regarding NLP in both the philosophical and the pedagogical aspects. This review suggests that there exist the bridging links between NLP, its philosophical foundation and pedagogy through certain theories like Constructivism and Information Processing. Some pedagogical relevance of NLP is also discovered in catering to its widespread into the educational world at all levels. Besides offering practicable knowledge to the teaching and learning stakeholders, this article is anticipated to create a more dialogic discourse within the academia, especially to add to the dearth of the discussion pertaining to NLP in philosophy and pedagogy.